2015
DOI: 10.1080/00140139.2015.1076057
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared spectroscopy as a tool for driving research

Abstract: Driving a motor vehicle requires various cognitive functions to process surrounding information, to guide appropriate actions, and especially to respond to or integrate with numerous contextual and perceptual hindrances or risks. It is, thus, imperative to examine driving performance and road safety from a perspective of cognitive neuroscience, which considers both the behaviour and the functioning of the brain. However, because of technical limitations of current brain imaging approaches, studies have primari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 79 publications
1
44
1
Order By: Relevance
“…The p values were obtained using Student's t-distribution with the assumption of bivariate normal distribution. A positive correlation was found between the beta power modulation (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) and the reaction time (ρ = 0.2 and 0.18 for FCz and CPz respectively), suggesting that the faster the reaction, the more decrease in beta. However, these correlations were not statistically significant (p > 0.05).…”
Section: Driver's Response Variabilitymentioning
confidence: 94%
See 1 more Smart Citation
“…The p values were obtained using Student's t-distribution with the assumption of bivariate normal distribution. A positive correlation was found between the beta power modulation (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) and the reaction time (ρ = 0.2 and 0.18 for FCz and CPz respectively), suggesting that the faster the reaction, the more decrease in beta. However, these correlations were not statistically significant (p > 0.05).…”
Section: Driver's Response Variabilitymentioning
confidence: 94%
“…Interestingly, some research groups have evaluated the possibility of applying transfer learning methods to reduce the amount of subject-specific data required to calibrate the EEG decoder [8], [9]. Recent studies performing simultaneous EEG and functional nearinfrared spectroscopy (fNIRS) recordings showed promising results on the use of the latter modality to obtain information about driver's drowsiness [17], [22]. Upon recognition of these mental states, the driving assistance system can make actions aimed at improving driver alertness [23].…”
Section: A Drowsiness Workload and Emergencymentioning
confidence: 99%
“…For example, the involvement of the medial PFC (mPFC) and the frontopolar cortex (Ayaz et al, 2012b ) and the inferior frontal gyrus (Harrison et al, 2014 ) was observed in subjects while executing air traffic control tasks; an activation of the overall frontal cortex was observed in subjects while performing a train piloting task (Kojima et al, 2005 ). Very recently, the usefulness of fNIRS as a tool to conduct driving research has been nicely reviewed (Liu et al, 2015 ). For example, an activation of the right PFC (Tomioka et al, 2009 ) and an activation of the overall PFC (Tsunashima and Yanagisawa, 2009 ) were found in subjects while executing different simulated car driving tasks.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Recent research shows that fatigue can be accurately identified through brain dynamics. [4][5][6][7][8][9] Therefore, brain activations in response to fatigue have become increasingly critical area of study over the past few decades. [7][8][9] Further, numerous studies have explored the relationships between brain oscillations and mental fatigue through tonic or phasic EEG changes.…”
Section: Introductionmentioning
confidence: 99%